Using Digital Transformation Strategies to Overcoming Adoption Barriers and Future Growth Opportunities Through The Mediating Role of Entrepreneurial Success: an Applied Study of A Sample of Employees in Small and Medium-Sized Enterprises Registered in The Diwaniyah Chamber of Commerce - Zainab Jassem Kareem; Omaima Ferman Tomas; Rasha Hameed Neamah (Research Parks Publishers, 2026)
The purpose of the current research is to use digital transformation strategies (DTS) represented in (technology, digitisation of processes, databases, human resources) to overcome adoption barriers and future growth opportunities (AFGO) by (administrative barriers, information technology barriers, financial barriers, employee-related barriers, environmental barriers) through the mediating role of entrepreneurial success (ES) represented in (financial dimension, entrepreneurial satisfaction, gratitude, entrepreneurial readiness) among a sample of employees in small and medium-sized companies registered in the Diwaniyah Chamber of Commerce by four companies (Horizon Gate Company for Electronic Devices Trading, Al-Daman Company for Smart Devices Trading, Al-Ghadeer Company for Electrical Appliances Trading, Al Burouj Company for Modern Paints Trading), In order to address the research problem of (What is the role of using digital transformation strategies in overcoming AFGO through the mediating role of entrepreneurial success?), the questionnaire tool was adopted to collect the necessary data, with (125) workers participating to detect the levels of research variables. After tabulating the data, it was found that the number of valid answers was represented in (97) individuals working in small and medium-sized companies registered in the Diwaniyah Chamber of Commerce. To analyse the results, two statistical packages were adopted (SPSS&AMOS. V.29), and accordingly, the results showed that digital transformation strategies contribute significantly to overcoming barriers of adoption and future growth opportunities with entrepreneurial success.